Enhancing Pre-service Teachers’ Procedural Fluency and Adaptive Reasoning in Trigonometry - Louis Robert C. Sison (Future Science / FSH-PH Publications, 2026)
This study examined the effects of Productive Struggle–Driven Creative Problem-Solving (PSD-CPS) instruction on the procedural fluency and adaptive reasoning of pre-service mathematics teachers in a trigonometry course at a public university in Malolos City, Bulacan. Using an embedded mixed-methods design, quantitative data from a quasi-experimental approach and qualitative data from reflective logs, observations, and focus group discussions were analyzed. Results showed significant posttest gains in both control and experimental groups. While procedural fluency gains were moderate, PSD-CPS instruction greatly enhanced adaptive reasoning. Participants positively perceived PSD-CPS as effective in improving their trigonometric understanding.